Determination of Kinetic Parameters and Formation Constants of In(III)-{3-Hydroxy-3-o-Tolyl-1-(p-Carboxy-phenyl) Triazene} (HOTCPT) and In(III)-{3-Hydroxy-3-Ethyl-1-(p-Carboxyphenyl) Triazene} (HECPT) Complexes& - Kumar Lohiya, Rajendra; Mukherji, S.K.; Singh, R.V. (Asian Journal of Chemistry, 2010)
The interaction of In3+ with hydroxy triazene has been studied at dropping mercury electrode at a constant ionic strength. The reductions were diffusion controlled but quasi-reversible. The Er1/2 have been obtained by Gelling's method and the formation constants of the complexes formed have been evaluated by Deford and Hume's method. In(iii) forms four complex species with 3-hydroxy-3-o-tolyl-1-(p-carboxyphenyl) triazene (HOTCPT) and 3-hydroxy- 3-ethyl-1-(p-carboxyphenyl) triazene} (HECPT) ions having β1 = 5.5 X 1012, β2 = 7.1 X 1013, β3 = 50 X 1014, β4 = 384 X 1014 and β1= 1.2 x 1012, β2 = 4 X 1013, β3 = 112 X 1015, β4 = 8.8 x 1018.respec_ tively. The kinetic parameters have been calculated by Meites and Israel method. The value of Ks comes of the order of 104 cm sec -1 confirming the quasi-reversible nature of the electrode process. With increase in complexing agent concentration, the value of Ks slightly decreases indicating the increase irreversibility of the electrode process.